Pemeriksaan Gula Darah Sewaktu dan Penyuluhan Kesehatan tentang Diabetes Militus pada Lansia di Tatabau - Sepang, Janice; Restawan, I Gede; Kantohe, Imelda (Universitas Baiturrahim, 2025)
Diabetes Mellitus (DM) is a disease that is still a health problem in the world. Undetected and uncontrolled DM in the elderly can cause various serious complications that reduce quality of life and increase morbidity and mortality. This community service activity was carried out on December 16, 2024 in Tatabau Village, South Buko District, Banggai Islands Regency, Central Sulawesi Province, involving 25 elderly people. The aim of this activity is to increase elderly knowledge about diabetes mellitus and the importance of regular blood sugar checks. The method used was temporary blood sugar (GDS) examination and counseling on diabetes mellitus through lectures and brochure media. The activity stages began with preparation, opening, and pretest of elderly knowledge. Next, GDS examination was carried out to determine blood glucose levels and diabetes risk. The material was delivered by the resource person, followed by a question and answer session, and ended with a post-test to measure the increase in knowledge. The examination results showed an average GDS of 120.2 mg/dL, with 8% of the elderly having GDS ≥200 mg/dL. Elderly knowledge about diabetes increased from 36% to 84% after counseling. This activity proves that health counseling with lecture and brochure methods is effective in increasing elderly knowledge about diabetes mellitus, as well as the importance of regular check-ups to prevent diabetic complications. These findings provide a basis for future sustainable health education programs.